Development of Children's Literacy Skills Using Loose Parts to Enhance Teachers' Understanding at Tk ABA Kartini Binjai - Rozana, Salma; Widya , Rika; Ependi, Rustam; Yanti, Nursaida (The Future of Education Journal, 2024)
This study aims to enhance teachers' understanding of developing language literacy skills in young children. The research method uses a qualitative approach with a literature review technique, examining scientific papers, books, and other written materials on the role of teachers in stimulating language literacy in early childhood. Based on the findings, it is clear that every teacher must have a correct understanding of literacy competence in order to effectively teach literacy to their students, specifically young children. The study concludes that there are 10 components that teachers need to understand regarding their role in developing early childhood language literacy with loose parts. These components include: teacher knowledge and experience; a basic understanding of literacy; engaging in lively discussions; using books; using the alphabet; training phonological awareness; building a language-rich environment; using loose part media; assessing children's literacy progress; and collaborating with parents. Loose parts, or materials commonly known as "loose parts," are learning tools that offer children the opportunity to explore, manipulate, or critically exploit their imagination, as the characteristics of loose parts allow children to shape them according to their ideas. The subjects of this study are young children at TK ABA Kartini Binjai.